TREM2 shedding by cleavage at the H157‐S158 bond is accelerated for the Alzheimer's disease‐associated H157Y variant. Issue 10 (30th August 2017) - Thornton, Peter; Sevalle, Jean; Deery, Michael J; Fraser, Graham; Zhou, Ye; Ståhl, Sara; Franssen, Elske H; Dodd, Roger B; Qamar, Seema; Gomez Perez‐Nievas, Beatriz; Nicol, Louise SC; Eketjäll, Susanna; et al.
Abstract: We have characterised the proteolytic cleavage events responsible for the shedding of triggering receptor expressed on myeloid cells 2 (TREM2) from primary cultures of human macrophages, murine microglia and TREM2‐expressing human embryonic kidney (HEK293) cells. In all cell types, a soluble 17 kDa N‐terminal cleavage fragment was shed into the conditioned media in a constitutive process that is inhibited by G1254023X and metalloprotease inhibitors and siRNA targeting ADAM10. Inhibitors of serine proteases and matrix metalloproteinases 2/9, and ADAM17 siRNA did not block TREM2 shedding. Peptidomimetic protease inhibitors highlighted a possible cleavage site, and mass spectrometry confirmed that shedding occurred predominantly at the H157‐S158 peptide bond for both wild‐type and H157Y human TREM2 and for the wild‐type murine orthologue. Crucially, we also show that the Alzheimer's disease‐associated H157Y TREM2 variant was shed more rapidly than wild type from HEK293 cells, possibly by a novel, batimastat‐ and ADAM10‐siRNA‐independent, sheddase activity. These insights offer new therapeutic targets for modulating the innate immune response in Alzheimer's and other neurological diseases. Synopsis: Sequence variation in the microglial receptor protein TREM2 is linked to risk for Alzheimer's disease. The disease‐linked H157Y variant of TREM2 is found to affect the sheddase site and accelerates proteolytic loss of TREM2 from the cell surface. TREM2 was shed rapidly from primary macrophages and microglia under basal conditions. The sheddase site was identified using peptidomimetic inhibitors and mass spectrometry. The Alzheimer's disease‐linked H157Y TREM2 sheddase‐cleavage‐site variant was shed more rapidly than wild type. For both wild type and variant TREM2 the major sheddase was ADAM10, however an additional proteolytic activity might be recruited by the H157Y variant. The protection of TREM2 from proteolysis might represent a novel therapeutic approach. Abstract : Sequence variation in the microglial receptor protein TREM2 is linked to risk for Alzheimer's disease. The disease‐linked H157Y variant of TREM2 is found to affect the sheddase site and accelerates proteolytic loss of TREM2 from the cell surface.